Conservação de grãos de pólen e estudos reprodutivos em Bromeliaceae - Souza, Sandra de Oliveira (2025)
The conservation of biodiversity and the reproductive management of species, especially threatened ones, are central challenges for maintaining the genetic richness of plants. In the case of Bromeliaceae, many taxa exhibit asynchronous flowering, microendemism, and reproductive barriers that can compromise the production of viable seeds, hindering conservation strategies and genetic improvement programs. In this context, understanding reproductive systems and developing efficient methods for pollen grain conservation are fundamental to ensuring the persistence of populations and the protection of the genetic heritage of these species. This thesis aimed to deepen the knowledge about the conservation of pollen grains and the reproductive systems of Bromeliaceae species, providing scientific support to guide conservation and management actions. The work is structured in two chapters. The first study, entitled “Cryopreservation for the establishment of a cryobank of pollen grains from endangered species of Lymania Read (Bromeliaceae) endemic to Northeast Brazil”, aimed to define the best conditions for dehydration and storage of pollen grains to enable their long-term conservation. Eight Lymania species were evaluated, subjecting the pollen grains to different periods of dehydration in silica gel and storage in a freezer (-5°C) and cryopreservation in liquid nitrogen (-196°C). Viability was analyzed in vitro and in vivo, and fruit and seed production and germination were monitored, with acclimatization of the regenerated plants. The results showed that the pollen grains remained viable after 365 days of cryopreservation, with viability above 89.5% and pollen tube length greater than 0.97 mm. Freezer storage compromised viability after 30 days. In vivo pollinations resulted in high fruit set (>75%) and viable seeds, with germination starting on the fourth day and stabilizing around 15 days. The survival rate of plants after acclimatization was greater than 89%, allowing the implementation of a functional cryobank. The second chapter, entitled "Reproductive systems of Tillandsia L. (Bromeliaceae) species occurring in the State of Bahia, Brazil," aimed to identify the reproductive systems of 14 species, evaluate pre- and post-zygotic barriers, and quantify fruit set and germination after controlled crosses. Experiments were conducted on natural pollination, spontaneous selfpollination, artificial self-pollination, cross-pollination, and verification of agamospermy, with analysis of pollen tube growth by fluorescence microscopy and in vitro germination of the generated seeds. The results indicated a predominance of allogamy, with ten species exhibiting mixed systems and four species being obligate allogamous. No species exhibited agamospermy. Cross-pollination resulted in fruit set exceeding 80% and up to 359 seeds per fruit, while the seeds showed high germination (≥77%) and seedling vigor, regardless of the reproductive system. Taken together, the findings demonstrate broad reproductive flexibility in the genus Tillandsia and show that cryopreservation is an efficient tool for conserving Lymania pollen grains, offering valuable support for conservation strategies and reproductive management, especially for endemic and threatened species in Brazil.